(3QSGdI aj eYQaI WQjb Gdhab GdeNeS GdNGdj GdhSWs - (3eMeO Hf GdMSf Hf eMeO Hf jhSa GdaGSj GdebQj, CHh YHO Gddg,J (B672 (3g` s ((3eUWai Hf jhfS s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ Edi Gddg GdZfj eMeO GdaGSj gPg fHPg ef Yde Gdhab GdoeNeS GdNGdj GdhSW s
(3BNQgG (B:s
(3gPg GdCedGc hGdCYhGf eKd HSe Gddg GdQMef GdQMje Gddge Efj CSCdc jGGddg GdCdaI JeJ hHGdNjQ YefJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3HZOGO (B(453) s
Keywords: (3GdMQha h GdChaGbs